2009
DOI: 10.1105/tpc.109.069757
|View full text |Cite
|
Sign up to set email alerts
|

Cotranslational Proteolysis Dominates Glutathione Homeostasis to Support Proper Growth and Development  

Abstract: The earliest proteolytic event affecting most proteins is the excision of the initiating Met (NME). This is an essential and ubiquitous cotranslational process tightly regulated in all eukaryotes. Currently, the effects of NME on unknown complex cellular networks and the ways in which its inhibition leads to developmental defects and cell growth arrest remain poorly understood. Here, we provide insight into the earliest molecular mechanisms associated with the inhibition of the NME process in Arabidopsis thali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 72 publications
2
39
0
Order By: Relevance
“…This effect can be fully recapitulated by site-directed substitutions altering N-Met cleavage of the corresponding plastid target D2 protein. Very recently, it was shown that cytoplasmic NME downregulation (i.e., partial retention of the N-Met) in Arabidopsis triggers an increase in cellular proteolytic activity, initiated by an increase in the size of the pool of proteins suitable for processing (Frottin et al, 2009). This deregulation of proteolysis, driven by the increase in the free amino acid pool and NADPH depletion, perturbs the glutathione redox state and ultimately leads to the plant developmental defects observed when cytoplasmic NME is impaired.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect can be fully recapitulated by site-directed substitutions altering N-Met cleavage of the corresponding plastid target D2 protein. Very recently, it was shown that cytoplasmic NME downregulation (i.e., partial retention of the N-Met) in Arabidopsis triggers an increase in cellular proteolytic activity, initiated by an increase in the size of the pool of proteins suitable for processing (Frottin et al, 2009). This deregulation of proteolysis, driven by the increase in the free amino acid pool and NADPH depletion, perturbs the glutathione redox state and ultimately leads to the plant developmental defects observed when cytoplasmic NME is impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the cytoplasmic NME is essential for normal growth and development of Arabidopsis. NME orchestrates a crosstalk between two fundamental signaling pathways that are frequently deregulated under pathological conditions: thiol status and proteolysis (Ross et al, 2005;Frottin et al, 2009). In all studied compartments, the developmental defects induced by NME inhibition seem to be caused by increased cellular proteolytic activity, primarily induced by an increase in the number of proteins targeted for rapid degradation (Frottin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant increase in GSSG levels during the early stages of development was also reported during the differentiation of tracheary elements in Zinnia sp. cells and Arabidopsis thaliana roots (Henmi et al 2005) and seedlings (Frottin et al 2009). The reduction potential is also dependent on the concentration of total glutathione ([GSH] ?…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that GSH involved in root development that control nutrients' uptake and the growth of plants. In this connection, glutathione-deficient mutant, chlorinal-1 (ch1-1), shows that GSH influenced the growth and physiology of the mutant (Frottin et al, 2009;Jahan et al, 2014). Glutathione synthesis is necessary for germination of pollen in vitro (Zechmann et al, 2011).…”
Section: The Role Of Glutathione In Plantsmentioning
confidence: 99%